Perceived ethical leadership in relation to organisational justice and organisational citizenship behaviour at a selected municipality in the Limpopo Province - Nethavhani, Andani (My University, 2023)
The purpose of this study is to investigate the relationship between ethical leadership, organisational justice, and organisational citizenship behaviour in a selected municipality in the Limpopo Province. A quantitative research design was used in which self-administered questionnaires were utilised to collect data from a convenience sample of 120 participants. The sample size constituted of 120 employees from 1 municipality, drawn from a population of (n=174) employees. The data was collected using the Ethical Leadership Questionnaire (EQL), the Organisational Justice Questionnaire (OJQ) and the Organisational Citizenship Behaviour Questionnaire (OCBQ). Descriptive statistics such as mean, mode, and median and inferential statistics, including correlation and regression analyses were used during data analysis. These were chosen to provide basic information about variables and also to highlight potential relationships between the variables. The findings indicated that there is a positive relationship between ethical leadership, organisational justice, and organisational citizenship behaviour. The results revealed that employees do not perceive fairness in the workplace, they do not see the existence of ethical leadership and they are less motivated to engage in extra-role behaviours. It was recommended that leaders should promote ethical behaviours, ensure that there is fairness in the organisation in order to encourage employees to engage in extra-role behaviours. The study recommends further research on the perceptions of employees on the three variables
Thesis (M.Com. (Human Resource Management)) -- University of Limpopo, 2023
Keywords: Ethical leadership; Organisational Justice; Social exchange; Distributive justice; Organisational citizenship behaviour; Leadership -- Moral and ethical aspects; Social exchange; Organizational justice